Anatomical and physical properties of tendril perversion of Coccinia grandis (L.) Voigt - T Prombanchong; A Suriyawong; P Srisongkram; N Suwanpayak (My University, 2020)
Abstract The structure of biomaterial is interest in biomimetic and biomechanics research. The physical properties, mechanical, characteristic of twisting and bending of plant tendrils are also thought-provoking to study. In this study, we proposed an innovative biomaterial spring device for holding an object and providing support. The device uses Coccinia grandis (L.) Voigt tendril as inspired by the relations of left-hand (LH) and right-hand (RH) climbing tendrils with a single branch. To study the morphology and anatomy, testing stress, length, number of the helix of the tendril which relation of mimic string material Coccinia grandis (L.) Voigt tendril and helical metal which have two helixes, three helixes and four helixes were tested by using food texture analysis. The anatomical showed many cell types and slight differences between straight and coiled tendrils. The result showed the tendril of two helixes has the highest stress and four helixes the least. Also, tensile testing showed that the number of helixes does not affect the stress of the tendril models.
Keywords: Tendril; Ramachandran plot; Tree Root and Stability Studies